Mobiliser par le consentement : la communication du gouvernement suisse durant la COVID-19 - Sébastien Salerno; Patrick Amey (Communiquer)
This study focuses on the narrative held by the Federal Council from April 10th to April 18th, 2020, seen as a pivotal moment for COVID-19 restrictions in Switzerland. In this decisive period, what kind of narrative was produced by the Government of Switzerland regarding COVID-19? We answer this question through an analysis of the Federal Council's messages published on Twitter for the above-mentioned period. This analysis shows that Federal Council's tweets lean on a rhetoric of consent. By establishing measures in order to face the sanitary crisis, the Federal Council, through the President's voice, chose to promote a virtuous consent bond with the population. As of the Health Minister, his communications were oriented towards ongoing actions, avoiding calling to fear or culpability.